Orthotopic transplantation of a tissue engineered diaphragm in rats. (January 2016) - Gubareva, Elena A.; Sjöqvist, Sebastian; Gilevich, Irina V.; Sotnichenko, Alexander S.; Kuevda, Elena V.; Lim, Mei Ling; Feliu, Neus; Lemon, Greg; Danilenko, Konstantin A.; Nakokhov, Ramazan Z.; Gumenyuk, Ivan S.; Grigoriev, Timofei E.; et al.
Abstract: The currently available surgical options to repair the diaphragm are associated with significant risks of defect recurrence, lack of growth potential and restored functionality. A tissue engineered diaphragm has the potential to improve surgical outcomes for patients with congenital or acquired disorders. Here we show that decellularized diaphragmatic tissue reseeded with bone marrow mesenchymal stromal cells (BM-MSCs) facilitates in situ regeneration of functional tissue. A novel bioreactor, using simultaneous perfusion and agitation, was used to rapidly decellularize rat diaphragms. The scaffolds retained architecture and mechanical properties and supported cell adhesion, proliferation and differentiation. Biocompatibility was further confirmed in vitro and in vivo . We replaced 80% of the left hemidiaphragm with reseeded diaphragmatic scaffolds. After three weeks, transplanted animals gained 32% weight, showed myography, spirometry parameters, and histological evaluations similar to native rats. In conclusion, our study suggested that reseeded decellularized diaphragmatic tissue appears to be a promising option for patients in need of diaphragmatic reconstruction.